The Effect of Annealing Temperatures on Structural Properties of Cu2O Nanoparticles - ِAlsoltani karrar A.; H. Harbbi, Khalid (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
In this study, the effect of the annealing temperature on the material properties and the structural properties of cuprous oxide was studied in order to investigate how the annealing temperature affects the material properties, and the temperature varied between 200℃, 300℃, 400℃ and 500 ℃ and was unannealed. The physical properties of the cuprous oxide were measured by X-ray diffraction (XRD). The XRD patterns showed that the Cu2O nanoparticles were highly pure, crystalline, and nano-sized. From the XRD results, we found the pure cuprite (Cu2O) phase. The values of crystal size were discovered and calculated by the Halder-Wagner and Size-Strain Plot (SSP) methods, respectively. The crystallite size increased as the annealing temperature increased. As a result, it was discovered that annealing temperature has a significant impact on structural and morphological aspects. In order to calculate physical and microstructural parameters such as internal strain, dislocation density, surface area, and consequently the number of unit cells, the sample was taken into consideration.